SINTESIS SENYAWA RISINOLEIL DIETANOLAMIDA MELALUI REAKSI AMIDASI ASAM RISINOLEAT DENGAN DIETANOLAMINA - Suci Amalia (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
There was a synthesis of derived amida of risinoleat acid compound through amidasi reaction. Risinoleat Acid obtained through metil risinoleat isolation from jarak oil through trans-esterifikasi reaction using natrium metoksida, and then doing hidrolisis metil risinoleat. Amidasi reaction to risinoleat acid was obtained by adding dietanolamina to the high temperature during 6 hours. Structure confirmation from the result compound is characterized by spektrometer IR and GC-MS.Amidasi risinoleat acid reaction and dietanolamina produce risinoleil dieanolamida compound as like thick liquid, chocolate yellowness coloured with rendemen 45,26 %. The lost of acid karbonil cluster absorption from analysis IR result to alkanolamida compound cannot convince that amida compound is 100% formed. Key words: risinoleat acid, dietanolamina, amidasi reaction, jarak oil